Experience capitalization: Editing starts by organising information - Rocha de Araujo, Marta (Technical Centre for Agricultural and Rural Cooperation, 2019)
A couple of months ago I was invited to join a group of participants starting a capitalization process in Maputo, Mozambique, and to help them edit the texts they were preparing. I had read many similar articles coming out of previous workshops, but I had never followed such a workshop myself before.